2000
DOI: 10.1111/1467-9523.00158
|View full text |Cite
|
Sign up to set email alerts
|

Food Supply Chain Approaches: Exploring their Role in Rural Development

Abstract: T he creation, operation and evolution of food supply chains are one key dimension in the new patterns of rural development now emerging (see Marsden 1998). As a result this dimension -the food chain dimension -becomes a significant building block for a new theory of rural development. This paper explores some of the key aspects of the food supply chain approach, making a direct link between theory and practice. To more fully understand the role and potential of food supply chains in the process of rural devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
624
0
165

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 892 publications
(807 citation statements)
references
References 7 publications
18
624
0
165
Order By: Relevance
“…Third, the rapid pace of industrialization, market integration and consolidation in global food systems has greatly enhanced the connectivity and interdependence of lengthy food supply chains, and the relationships of food chains with other industries -such as that of energy -while typically concentrating key resources (technology, research and development, distribution channels, marketing) in fewer hands (Clapp 2011;Lang 2003). Fourth, while nutritional deficiencies and food access remain challenging in many parts of the world, new issues have emerged associated with the maintenance of food quality and safety, exacerbated by problems in transparency, convoluted and long supply chains, and the volume of information that must be processed and evaluated by consumers (Marsden et al 2000;McMichael 2006). Finally, in the modern era of such long supply chains, food and agriculture concerns have been governed separately: production, consumption, distribution, processing and waste management have been considered as separate concerns with distinct actors, interests and institutional relations, yet disturbance or crisis on one domain has significant repercussions in others.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the rapid pace of industrialization, market integration and consolidation in global food systems has greatly enhanced the connectivity and interdependence of lengthy food supply chains, and the relationships of food chains with other industries -such as that of energy -while typically concentrating key resources (technology, research and development, distribution channels, marketing) in fewer hands (Clapp 2011;Lang 2003). Fourth, while nutritional deficiencies and food access remain challenging in many parts of the world, new issues have emerged associated with the maintenance of food quality and safety, exacerbated by problems in transparency, convoluted and long supply chains, and the volume of information that must be processed and evaluated by consumers (Marsden et al 2000;McMichael 2006). Finally, in the modern era of such long supply chains, food and agriculture concerns have been governed separately: production, consumption, distribution, processing and waste management have been considered as separate concerns with distinct actors, interests and institutional relations, yet disturbance or crisis on one domain has significant repercussions in others.…”
Section: Introductionmentioning
confidence: 99%
“…''Local food'' stresses the spatial closeness of food production and consumption, and it comprises also the basic food products, the staples. ''Locality food'' stresses the origin of food and the value added associated with it (Marsden et al 2000); these are often labeled exclusive products targeted for international markets, and their consumers may be very far from the site of production. In general, rather than exporting food, the expansion of the food sector could rely more on exporting the food-related knowledge, technology and social innovations.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For example Marsden et al, (1999), Ross et al (1999), Marsden et al (2000), Hinrichs (2003), Winter (2003), and Ikerd (2005) have all suggested that expansion of local foods may be a development strategy for rural areas, particularly those areas that have experienced negative effects of globalization. And while many scholars have highlighted the importance of local food systems to regional economies (Feenstra 1997;Trobe 2001;Renting et al 2003;Star et al 2003;Bhatia and Jones 2011), few have sought to exploit recent theoretical frames advanced by researchers from the fields of economic geography and regional science; the fields most concerned with regional economic development.…”
Section: 1: Overviewmentioning
confidence: 99%
“…That is, local food supply chains strive to establish a bond between the producer and the consumer, even when separated by intermediary segments in the supply chain (Renting et al, 2003). Marsden et al (2000), describes three types of localized food supply chains: face-to-face, where consumers buy a product direct from the producer/processor on a face-to-face basis; spatially proximate, where products are sold through local outlets in the area and consumers are immediately aware of its local nature and; spatially extended, where products are sold to consumers who are located outside the local area and who may have no knowledge of that area. Here, the key is to use product labeling and imagery to transfer information about the production process and the area to the consumer (Ilbery et al, 2003).…”
Section: Chainsmentioning
confidence: 99%